2021
DOI: 10.1186/s12933-021-01426-z
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced weight loss in obese/diabetic mice normalizes glucose metabolism and promotes functional recovery after stroke

Abstract: Background Post-stroke functional recovery is severely impaired by type 2 diabetes (T2D). This is an important clinical problem since T2D is one of the most common diseases. Because weight loss-based strategies have been shown to decrease stroke risk in people with T2D, we aimed to investigate whether diet-induced weight loss can also improve post-stroke functional recovery and identify some of the underlying mechanisms. Methods T2D/obesity was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 84 publications
1
14
0
Order By: Relevance
“…PPRF8 (pre-mRNA processing factor 8), a core component of the spliceosome, is an important mediator of hypoxia-induced mitosis 52 , and a high-fat diet upregulates the expression of genes related to the spliceosome 53 , increasing the risk of ischemic stroke. Adjusting the diet may enhance functional recovery after stroke by modulating insulin resistance and normalizing glucose metabolism 54 .…”
Section: Discussionmentioning
confidence: 99%
“…PPRF8 (pre-mRNA processing factor 8), a core component of the spliceosome, is an important mediator of hypoxia-induced mitosis 52 , and a high-fat diet upregulates the expression of genes related to the spliceosome 53 , increasing the risk of ischemic stroke. Adjusting the diet may enhance functional recovery after stroke by modulating insulin resistance and normalizing glucose metabolism 54 .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate mechanisms of neuroplasticity, we focused our studies on striatal cholinergic ChAT + interneurons, since these cells coordinate the firing of medium spiny neurons that in turn regulate motor output [ 38 ] and also regulate stroke recovery [ 39 ]. Other interneurons, such as those positive for Parvalbumin and Somatostatin, have been recently investigated in other studies from our group [ 17 , 25 , 26 , 29 , 34 ]. We recorded an overall increased number of ChAT + interneurons in IR-HG and IR-NG sham-operated mice versus healthy CTRL mice, likely indicating an upregulation of ChAT expression, making more cells detectable by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, insulin signaling in hypothalamic astrocytes controls CNS glucose sensing and systemic glucose metabolism via the regulation of glucose uptake across the BBB [ 64 ]. In relation to stroke recovery, we also recently showed that HFD feeding results in reduced astrocyte reactivity in association with impaired recovery [ 17 ]. It is therefore plausible that impaired insulin signaling in astrocytes plays an important role in decreased recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations